Case report: Anti-IgLON5 disease and anti-LGI1 encephalitis following COVID-19 - Li, Yanfei; Jia, Yanjie (Frontiers in Immunology, 2023)
Anti-IgLON5 disease is a rare autoimmune-mediated encephalitis, characterized by sleep problems, cognitive decline,gait abnormalities and bulbar dysfunction. Anti-leucine rich glioma inactivated 1 (LGI1) autoimmune encephalitis is characterized by cognitive impairment, psychiatric disorders, faciobrachial dystonic seizures (FBDS) and refractory hyponatremia. Coronavirus disease 2019 (COVID-19) has been reported to affect the nervous system which cause a wide range of neurological symptoms. Autoimmune encephalitis is one of the neurological complications in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection.Till now, autoimmune encephalitis with both anti-IgLON5 and anti-LGI1-receptor antibodies following COVID-19 is rarely reported.The case report described a 40-year-old man who presented with sleep behavior disorder, daytime sleepiness,paramnesia,cognitive decline,FBDS and anxiety following COVID-19. Anti-IgLON5 and anti-LGI1-receptor antibodies were positive in serum and anti-LGI1-receptor antibodies were positive in cerebrospinal fuid (CSF). The patient presented with typical symptoms of anti-IgLON5 disease such as sleep behavior disorder, obstructive sleep apnea and daytime sleepiness.Besides,he presented wih FBDS, which is common in anti-LGI1 encephalitis. Therefore, the patient was diagnosed with anti-IgLON5 disease and anti-LGI1 autoimmune encephalitis. The patient responded well to high-dose steroid and mycophenolate mofetil therapy. The case serve to increase the awareness of rare autoimmune encephalitis after COVID-19.